Politeness Strategies in Sister-to-Sister Interaction in Little Women by Louisa May Alcott - Dea Meinanda; Dyah Nugraheny Priastuti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study examines the politeness strategies used in interactions among sisters in Louisa May Alcott’s novel Little Women. Using Brown and Levinson’s (1987) politeness theory as an analytical framework, this study identifies and classifies the forms of politeness strategies that emerge in the conversations of the four main characters: Meg, Jo, Beth, and Amy March. The research data consists of dialogic utterances purposively selected from the novel’s text. The results indicate that all four politeness strategies on record, positive politeness, negative politeness, and off record are present in the interactions among the sisters, with positive politeness being the most dominant. The dominance of this strategy reflects the closeness of their relationship, solidarity, and mutual respect among the characters. Additionally, the choice of politeness strategies is also influenced by factors such as social distance, age differences, and situational context. This study contributes to the understanding of language use in a literary context, particularly in depicting the dynamics of family relationships through character interactions.